Information Sharing in a Supply Chain: A Note on its Value when Demand Is Nonstationary - Raghunathan, Srinivasan (Management Science, 2001)
In a recent paper, Lee, So, and Tang (2000) showed that in a two-level supply chain with non-stationary AR(1) end demand, the manufacturer benefits significantly when the retailer shares point-of-sale (POS) demand data. We show in this paper, analytically and through simulation, that the manufacturer's benefit is insignificant when the parameters of the AR(1) process are known to both parties, as in Lee, So, and Tang (LST). The key reason for the difference between our results and those of LST is that LST assume that the manufacturer also uses an AR(1) process to forecast the retailer order quantity. However, the manufacturer can reduce the variance of its forecast further by using the entire order history to which it has access. Thus, when intelligent use of already available internal information (order history) suffices, there is no need to invest in interorganizational systems for information sharing.